Pengaruh Gaya Kepemimpinan Kepala Sekolah, Dan Sistem E-Kinerja Terhadap Kinerja Guru Dengan Disiplin Kerja Sebagai Intervening Pada Sekolah Menengah Pertama 24 Padang - Salsabila, Dhea Arza; Kumbara, Vicky Brama; Nadilla, Nia (CV. ITTC INDONESIA, 2026)
This study aims to examine the extent to which the principal’s leadership style and the E-Performance System influence teacher performance with work discipline as an intervening variable at Junior High School 24 Padang. The study used SPSS version 23 for data processing. The population consisted of 53 employees, and a saturated sampling technique was applied. Data were collected using documentation techniques. The data analysis employed outer loading tests, inner model analysis, and hypothesis testing. The results show that the principal’s leadership style has an effect on teachers’ work discipline at SMP Negeri 24 Padang, while the E-Performance System does not have an effect on work discipline. The principal’s leadership style also influences teacher performance, whereas the E-Performance System does not affect teacher performance. Work discipline influences teacher performance. Work discipline mediates the effect of the E-Performance System on teacher performance. Work discipline does not mediate the effect of the principal’s leadership style on teacher performance...